Modifikasi Makceting (Makanan Cegah Stunting) sebagai Bentuk Inovasi PMT di Desa Dorolegi Kecamatan Godong Kabupaten Grobogan - Wahyu Unggul Widodo; Deart Are Koeanda; Ahmad Yusuf Mufarihin; Eva Wulan Dari; Indah Fitriani; Alif Putra Dirgantara; Nurul Fahrian; Ayu Avitasari; Lutfia Atika Salma; Nova Ayyunda Sholehkhah (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2026)
Stunting is a chronic nutritional problem that impacts physical growth, cognitive development, and the quality of human resources. The high prevalence of stunting in Grobogan Regency requires innovative and sustainable community-based interventions. One preventative measure is through the provision of supplementary feeding (PMT) based on local foods with high animal protein content. This activity aims to increase the knowledge and awareness of mothers of toddlers regarding the importance of animal protein intake through the PMT innovation "MAKCETING (Food to Prevent Stunting)" with the Hidden Egg food product. The method used was education and reflection on PMT making for PKK members in Dorolegi Village, Godong District, Grobogan Regency, which involved 100 participants and was implemented by KKN (Community Services Program) students from An Nuur University Purwodadi. The product was developed from chicken meat, quail eggs, and carrots. The results of the activity showed a positive response, high enthusiasm, and increased understanding of participants regarding the importance of animal protein in preventing stunting.